Outcomes harvesting, Digital Agriculture Project - Camacho, Kemly (2021)
This document presents the results of the evaluation of the Digital Agriculture project. The methodology known as outcome harvesting was used, which is a tool that allows to identify, monitor and learn about the changes of various actors involved in the implementation of the project. With the results it was possible to evaluate the significance of changes in the stakeholders and how the project contributed to this change.